Feedback is Integral: Using a Revised ICAP Framework to Achieve Active Learning in an Asynchronous Online Course - Pollard, Vikki; Armatas, Christine; Pepe, Avni (Online Learning, 2025)
The Interactive, Constructive, Active, Passive (ICAP) Framework (Chi & Wylie, 2014) is used to review and develop active learning in higher education. It is a hierarchical model based on overt behaviours seen by the teacher in the classroom. This principle is acknowledged as a limitation, especially in the case of online modes of study. In this paper, we revise the ICAP Framework to fit an asynchronous mode of online learning by introducing formative feedback to each ICAP mode, arguing the most active mode results in a student-produced output with evidence of having reflected on feedback. We then use the revised framework to review a course of study consisting of eight units of an asynchronous online post-graduate degree and then recommend ways in which to apply the revised ICAP Framework more generally to enhance the level of active learning in the asynchronous, online mode.